HUBUNGAN ANTARA KARAKTERISTIK BETON MENGGUNAKAN AGREGAT KASAR LIGHTWEIGHT EXPANDED CLAY AGGREGATE (LECA) - Sudarsana, I Ketut; Astawa Diputra, I Gede; Ari Astuti, Ni Made Dwi (JURNAL SPEKTRAN, 2018)
Lightweight concrete is a concrete made of lightweight aggregates and has a volume weight ranging from 1140-1840 kg/m 3 . This research was conducted to find out the correlation between concrete characteristics using LECA coarse aggregate that proportioned for lightweight concrete mixture according to SNI 03-3449-2002 standard with target compressive strength of 20 MPa, 25 MPa, and 30 MPa. The studied characteristics of the LECA concrete include the value of slump, volume weight, compressive strength, tensile strength, and modulus of elasticity. Each mix proportion was made 8 cylinder specimens of ASTM standard, so there were 24 test specimens for the three studied mixtures. The proportion of concrete mixture obtained for the target strength of 20 MPa is 1: 1.16: 2.46 with the value of cement water ratio (w/c) of 0.6, for the concrete strength of 25 MPa is 1: 0.91: 1.99 with the w/c of 0.52, and for the quality of the strength of 30 MPa is 1: 0.65: 0.94 with the w/c of 0.4. The test results obtained the mixed slump value of 155 mm, 145 mm, and 120 mm for the target concrete strength of 20 MPa, 25 MPa, and 30 MPa, respectively. The volume-weight value of LECA concrete ranges from 1564-1692 kg/m 3 so that it is categorized as a lightweight concrete. The concrete compressive strength is 22 to 42% of the target concrete strength, and is categorized as a non-structural concrete. The split test tensile strength is 12 - 18% of its compressive strength. Increasing the value of LECA concrete compressive strength can also increase in its tensile strength and modulus of elasticity.   Keywords : lightweight concrete, LECA aggregate, concrete characteristics, compressive strength, tensile strength.